The Influence of Cooperative Learning Accompanied By Image Media on The Initial Writing Ability of Grade 1 Elementary School Students In Terms of VAK Learning Style - Kulsum, Umi; Usman, Moh. Uzer; Juhana, Juhana (Journal Research of Social Science, Economics, and Management, 2023)
Media learning can be disadvantaged into four types, namely: (1) Visual media, which only relies on students’ senses of sight; (2) Audio media, which only involves students’ hearing, (3) Audiovisual media, which involves hearing and sight simultaneously in one process or activity; and (4) Multimedia, which involves several types of media and equipment in an integrated manner in a learning process or activity. This study aims to analyze the effect of the application of cooperative learning using visual media on the beginning writing ability of first graders of elementary school in terms of VAK (Visual, Auditory, Kinesthetic) learning styles through a quantitative approach with a quasi-experimental nonequivalent control group design. Data analysis was carried out using the t-test (t-independent samples) on the n-gain control class and the experimental class. The results showed that there was an effect of the application of cooperative learning with picture media on the initial writing ability for 1st-grade elementary school students in terms of VAK (Visual, Auditory, Kinesthetic) learning styles with the highest effect seen in students with kinesthetic learning styles.